Capturing the public imagination: Communicating the cultural significance of submarine internet cables - Holloway-Smith, B (SubOptic 2016)
Popular terms such as “wireless”, “the cloud”, and “cyberspace” have misled public perceptions of internet infrastructure, belying its physical and geographically-bound reality. This can cause problems for the submarine cable industry, particularly when explaining the infrastructure of the internet to uninformed potential investors, regulators, and the public in general. As an independent forum art can be a useful mediator in these situations, enabling shifts in these perceptions of the internet. This paper discusses a range of artworks that present new perspectives on submarine internet cables from outside the industry.